2017
DOI: 10.1111/jfpp.13252
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical solvent extraction of total anthocyanins from dried purple waxy corn: Influence of process conditions

Abstract: Total anthocyanin content in different dried parts of purple waxy corn (Zea mays L. var. ceratina) genotype Fancy Muang 111 was investigated under subcritical solvent extraction. The highest total anthocyanin content of 991.4, 1241.5, and 1552.1 µg cyanidin‐3‐glucoside per gram dry weight of sample were obtained from dried kernel extraction (water–ethanol at ratio 1:3 as solvent and sample–solvent at ratio 1:20), dried cob extraction (water–ethanol at ratio 1:1 as solvent and sample–solvent at ratio 1:20), dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…They found that the mean DPPH IC 50 value of purple corn cob extract was 40.1 μg/ml. Also Muangrat et al () reported the DPPH IC 50 value of 3.50 mg/ml for a dried cob extract obtained from purple waxy corn ( genotype Fancy Muang 111 ) when the dried cob was extracted under subcritical solvent extraction using water–ethanol at ratio 1:1 as solvent and sample–solvent at ratio 1:20 at 100 °C for 15 min with N 2 purging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the mean DPPH IC 50 value of purple corn cob extract was 40.1 μg/ml. Also Muangrat et al () reported the DPPH IC 50 value of 3.50 mg/ml for a dried cob extract obtained from purple waxy corn ( genotype Fancy Muang 111 ) when the dried cob was extracted under subcritical solvent extraction using water–ethanol at ratio 1:1 as solvent and sample–solvent at ratio 1:20 at 100 °C for 15 min with N 2 purging.…”
Section: Resultsmentioning
confidence: 99%
“…The stable organic free radical DPPH can be scavenged when encounter a proton donating substance such as an antioxidant, in order to reduce its absorbance. The scavenging activity of natural extracts produced from fruit, vegetable, or agro‐industrial wastes, can be detected via DPPH assay (Muangrat, Williams, & Saengcharoenrat, ; Ramos‐Escudero, Munoz, Alvarado‐Ortız, Alvarado, & Yanez, ; Sánchez‐Moreno, ; Yang & Zhai, , ). Additionally, the DPPH assay can accommodate many extract samples in a short period and is sensitive to detect active ingredients even at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…PWC cobs and seeds were ground in an electrical herb grinder separately, while boiled seed was steamed for 30 min before grinding and then extracted using either deionized water (DI water) or 70 % acetone as solvents with the sample:solvent ration of 25 g:1000 ml under 60º for 4 h. The extracts were filtered by Whatman no.1 filter paper to remove solid residual. About 0.1 % w/w ascorbic acid was added to protect oxidation before removing water by freezedrying at -30º under pressure 130 mbar for 72 h. The dried extracts were preserved at -20º [19,20] .…”
Section: Purple Corn Extractionmentioning
confidence: 99%
“…Antioxidant activity also determined by ferric reducing/antioxidant power (FRAP) assay. The antioxidant activity evaluated by FRAP was calculated as trolox equivalent (µM trolox/mg plant extract) [19,25] .…”
Section: Determination Of Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
“…Anthocyanins – water‐soluble polyphenol flavonoids – are often used as natural pigments in food production and processing, and they possess antioxidation, anti‐aging and anticancer properties, as well as providing liver and eyesight protection 5,6 . Moreover, PCC extract has been shown to have excellent antioxidant activity and inhibit C6 glioma cell proliferation in vitro 7,8 . It is of great significance to further develop the medicinal value of the waste purple corncobs.…”
Section: Introductionmentioning
confidence: 99%